The Current Approach to Diagnosis and Management of Left Ventricular Noncompaction Cardiomyopathy: Review of the Literature - Courtney E. Bennett; Ronald Freudenberger (Cardiology Research and Practice)
Isolated left ventricular noncompaction (LVNC) is a genetic cardiomyopathy characterized by prominent ventricular trabeculations and deep intertrabecular recesses, or sinusoids, in communication with the left ventricular cavity. The low prevalence of patients with this cardiomyopathy presents a unique challenge for large, prospective trials to assess its pathogenesis, management, and outcomes. In this paper we review the embryology and genetics of LVNC, the diagnostic approach, and propose a management approach based on the current literature available.